A regiocentric strategy for industrial clusters: reflections on international business innovations in the UAE. (2016) - Anwar, Syed Aziz
Cluster-oriented initiatives differ from traditional policy tracks pursued by a large number of Arab states in a significant manner. Traditional policy is based on a notion that some industries offer better prospects than others and hence must be protected until they acquire the necessary scale and sophistication to compete internationally on their own. Cluster initiatives, on the other hand, are designed on a more dynamic view of competition among firms and their coordination with associated institutions. A cluster-based regiocentric model adopted by the GCC countries does not seek entry barriers - be they against local or multinational enterprises. In fact, a cluster-oriented strategy highlights the challenge and the need for the timely and steady opening of the local market to imports of goods, services and technology, which in turn might improve supply chain (or value chain) efficiency, refine local demand conditions, and stimulate competition, resulting in a positive sum view of innovation-driven competitiveness. The GCC countries, most notably the UAE, have established free trade zones and industrial clusters to attract FDI. How important are clusters in a regiocentric context? This study suggests that the answer lies in innovation in international business.